Design, Manufacture of Water Distillation Equipment by Spraying Using Solar Energy - Nguyễn Hữu Nghĩa; Huỳnh Văn Thạo; Lương Đức Vũ; Nguyễn Văn Phúc (Journal of Technical Education Science, 2026)
Solar energy is considered a renewable energy source and is widely used in industry and life. This article presents the results of research on the design and manufacture of a water distillation device, using solar energy to heat seawater, combined with a spraying flash evaporation to collect fresh water, towards applications in saline intrusion areas. The device includes a solar collector with an area of 2 m2, a heating tank with a volume of 15 liters, a spray chamber with dimensions D x H = 52 x 65cm, spray pressure p = 3 bar, a spiral condenser with d = 6mm, l = 5m. The test results show that in the period from 8 am to 4 pm, the radiation intensity was from 300 to 1200 W/m2, the amount of fresh water collected was from 0,5 to 1,12 liters/h, the average electricity consumption was 0,433 kWh/liter. The research result suggests that the designing and manufacturing water distillation equipment at temperatures without boiling and combining with renewable energy to save energy.